2018
DOI: 10.1021/acsnano.8b06268
|View full text |Cite
|
Sign up to set email alerts
|

AA′-Stacked Trilayer Hexagonal Boron Nitride Membrane for Proton Exchange Membrane Fuel Cells

Abstract: Hexagonal boron nitride (h-BN) and graphene have emerged as promising materials for proton exchange membranes because of their high proton conductivity and chemical stability. However, the defects and grain boundaries generated during the growth and transfer of two-dimensional materials limit their practical applicability. Here, we report the fabrication of membrane electrode assemblies using large-area single-oriented AA′-stacked trilayer h-BN (3L-BN), which exhibits very few defects during the growth and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 25 publications
1
68
0
Order By: Relevance
“…Although the mechanism of proton transport is not clear, it does not affect the exploration of BN-based PEMFCs. [263][264][265][266] Kim and co-workers constructed a new electrode module and a fuel cell using trilayer h-BN (3L-BN) prepared by the low pressure CVD process (Figure 12d). [263] The characterization confirmed that the h-BN is a large-area single-oriented AA′ stack.…”
Section: Proton Exchange Membranementioning
confidence: 99%
See 2 more Smart Citations
“…Although the mechanism of proton transport is not clear, it does not affect the exploration of BN-based PEMFCs. [263][264][265][266] Kim and co-workers constructed a new electrode module and a fuel cell using trilayer h-BN (3L-BN) prepared by the low pressure CVD process (Figure 12d). [263] The characterization confirmed that the h-BN is a large-area single-oriented AA′ stack.…”
Section: Proton Exchange Membranementioning
confidence: 99%
“…[263][264][265][266] Kim and co-workers constructed a new electrode module and a fuel cell using trilayer h-BN (3L-BN) prepared by the low pressure CVD process (Figure 12d). [263] The characterization confirmed that the h-BN is a large-area single-oriented AA′ stack. At 10.08 mA cm −2 , the fuel cell with a monolayer BN membrane shows a high hydrogen permeable current density, indicating that gas transboundary flow occurs through the membrane, which may be attributed to intrinsic defects and grain boundaries in the monolayer.…”
Section: Proton Exchange Membranementioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, various clean energy conversion devices have been developed rapidly. Lithium ion batteries (LIBs), [2][3][4] solid oxide fuel cells (SOFCs), [5][6][7] proton exchange membrane fuel cells (PEMFCs), [8][9][10] metal-air batteries [11][12][13] and other clean and efficient devices have been continuously studied, fast developed and commercialized. For PEMFCs and metal-air batteries, the oxygen evolution reaction (OER) at the anode and oxygen reduction reaction (ORR) at the cathode are the main reactions of electrochemical conversion.…”
Section: Introductionmentioning
confidence: 99%
“…As a primary segment in the hydrogen energy chain, proton-exchange membrane fuel cells (PEMFCs) have also been regard as one of the most promising green energies due to high efficiency and pollution-free properties [8][9][10]. As the core component in a PEMFC, a proton-exchange membrane (PEM) acts as a proton-transporting medium and can directly affect the performance of a PEMFC [11,12]. For numerous developed PEMs, sulfonic acid (SA) groups are the most widely used functional groups due to the great proton conductive efficiency of SA groups with the assistance of water molecules at low temperature [13][14][15].…”
Section: Introductionmentioning
confidence: 99%